2017
DOI: 10.1111/1556-4029.13365
|View full text |Cite
|
Sign up to set email alerts
|

Prepartum Psychosis and Neonaticide: Rare Case Study and Forensic‐Psychiatric Synthesis of Literature

Abstract: Peripartum psychosis is a rare but serious psychiatric disorder characterized by the presence of a mood episode with psychotic features. Although controversy surrounds the nosological status of peripartum mental disorders, these conditions continue to be of exceptional interest to the medical and forensic mental health communities. The aim of this study was to report a rare case of prepartum psychosis which escalated to the endpoint of neonaticide and summarize literature on peripartum mental disorders and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…In addition to the physical challenges that pregnancy places on a woman’s body, it also increases a woman’s susceptibility to a variety of psychiatric conditions. These may include postpartum blues, peri- and postpartum depression, and brief psychotic disorder with peripartum onset [ 5 ]. The last of these encompasses both pre- and postpartum psychosis and has a recorded incidence rate of less than 0.5% with occurrence increased to 28% of women with a history of psychosis [ 6 - 8 ]; however, it is increasingly rare in women with no previous psychiatric history, such as this patient [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the physical challenges that pregnancy places on a woman’s body, it also increases a woman’s susceptibility to a variety of psychiatric conditions. These may include postpartum blues, peri- and postpartum depression, and brief psychotic disorder with peripartum onset [ 5 ]. The last of these encompasses both pre- and postpartum psychosis and has a recorded incidence rate of less than 0.5% with occurrence increased to 28% of women with a history of psychosis [ 6 - 8 ]; however, it is increasingly rare in women with no previous psychiatric history, such as this patient [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…These may include postpartum blues, peri- and postpartum depression, and brief psychotic disorder with peripartum onset [ 5 ]. The last of these encompasses both pre- and postpartum psychosis and has a recorded incidence rate of less than 0.5% with occurrence increased to 28% of women with a history of psychosis [ 6 - 8 ]; however, it is increasingly rare in women with no previous psychiatric history, such as this patient [ 5 ]. In fact, many consider brief psychotic disorder with peripartum onset to be a manifestation of an underlying psychiatric disorder, most commonly bipolar or schizoaffective disorder, and less commonly schizophrenia [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic construct of prior psychiatric history and treatment was in line with the known literature and the known risk factors for the development of postpartum psychosis . The findings further indicated that women who commit infanticide within the context of postpartum psychosis often receive psychiatric care; however, the care was deemed to be inadequate (Barnett, 2006;Karakasi et al, 2017;Koenen & Thompson, 2008). Inadequate care within the literature was perceived as hospitalisations which were too brief as well as inadequate psychoeducation (Spinelli, 2004).…”
Section: Psychiatric History and Treatmentmentioning
confidence: 99%
“…The findings of the synthesis further suggest that infants were often killed by the perpetrators using their hands. The most common methods of inflicting death were drowning, head trauma, suffocation, and strangulation (Barnett, 2005;Barnett, 2006;Karakasi et al, 2017;Smithey, 2001;State of Illinois v. Skeoch, 1951). Drowning was mentioned as the most common, mentioned in eight out of the 15 included studies; head trauma was discussed in five; and suffocation or strangulation in seven studies.…”
Section: Victims and Deathmentioning
confidence: 99%